2021
DOI: 10.1186/s13075-021-02589-6
|View full text |Cite
|
Sign up to set email alerts
|

First exposure to rituximab is associated to high rate of anti-drug antibodies in systemic lupus erythematosus but not in ANCA-associated vasculitis

Abstract: Background Anti-drug antibodies (ADAs) can impact on the efficacy and safety of biologicals, today used to treat several chronic inflammatory conditions. Specific patient groups may be more prone to develop ADAs. Rituximab is routinely used for ANCA-associated vasculitis (AAV) and as off-label therapy for systemic lupus erythematosus (SLE), but data on occurrence and predisposing factors to ADAs in these diseases is limited. Objectives To elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Specifically, there was a significant association between ARAs’ presence and titers and incomplete B-cell depletion in MS, and the ARA-positive group had a faster B-cell reconstitution in SDNS and MN ( 14 , 22 ). The count of CD19 + B cells after rituximab infusion in the ARAs group in SLE varied as Chris Wincup showed that no difference was found in CD19 + lymphocyte counts at the early and six-month time points between ARAs persistently positive and negative patients and Francesca Faustini reported that a higher proportion of CD19 + lymphocytes was seen in ARA-positive patients compared to ARA-negative patients ( 31 , 36 ). Moreover, most patients with MOGAD had a B-cell counts <1% at the time of disease activity ( 37 ) and B-cell counts have been found to be unrelated to clinical relapse in NMOSD ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there was a significant association between ARAs’ presence and titers and incomplete B-cell depletion in MS, and the ARA-positive group had a faster B-cell reconstitution in SDNS and MN ( 14 , 22 ). The count of CD19 + B cells after rituximab infusion in the ARAs group in SLE varied as Chris Wincup showed that no difference was found in CD19 + lymphocyte counts at the early and six-month time points between ARAs persistently positive and negative patients and Francesca Faustini reported that a higher proportion of CD19 + lymphocytes was seen in ARA-positive patients compared to ARA-negative patients ( 31 , 36 ). Moreover, most patients with MOGAD had a B-cell counts <1% at the time of disease activity ( 37 ) and B-cell counts have been found to be unrelated to clinical relapse in NMOSD ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The time‐dependent formation of antidrug antibodies (ADA) is known to accelerate the clearance of anti‐TNFα therapies and impair their efficacy in patients treated for inflammatory bowel disease (25). Regarding RTX, Faustini et al reported the lack of ADA in AAV patients (n = 41) while ADA presence was observed in 37.8% of patients treated for systemic lupus erythematosus (n = 62) (26). Given that the risk of immunogenicity seems very low in AAV patients with RTX, we decided not to investigate the formation of ADA as a determinant of PK variability as well as its association with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ADA was determined with an in-house validated electrochemiluminescence bridging assay (ECL) according to a previously described protocol (27,28).…”
Section: Anti-drug Antibodiesmentioning
confidence: 99%
“…The 15 patients analyzed in this study were also included in a recently published paper investigating the prevalence of antidrug antibodies (ADA) in our SLE cohort (28). In the mentioned paper, ADA positive SLE individuals showed higher B-cell counts at about six months follow-up with respect to ADA negative individuals.…”
Section: Comparative Analysis Of the B-and T-cell Autoimmunity Associ...mentioning
confidence: 99%